The Role of English on International Business Growth and Social Inequality - Cahya Budi Irawan; Meinarti Puspaningtyas; Ana Castellano; Danang Dwi Gusti Fajar Yanto (International Journal of Applied Business and International Management, 2022)
Our aim is to investigate the concept in previous research on Human Capital Concept in Education and Economics. We use Content Analysis to compile scientific articles from emerald, Science Direct, and Korean science as well as books written by experts in the field of English Education and Marketing. Digitalization is very important for companies and society to adapt. This digitalization is forcing organizations to explore new possibilities while continuing to use existing technologies in established companies. Companies need a marketing system to support the business. The ethical marketing system adopts an attitude that is consistent with the ethical and sustainable marketing concept and demonstrates courteous and ethical behavior to increase sales. English as an international language also plays an important role in supporting international marketing. The English education system has an impact on increasing the ability of students to use English